On the Book by Václav Bůžek on Ferdinand II, Archduke of Austria, and the Bohemian Aristocracy - Maťa , Petr (Dějiny – teorie – kritika, 2011)
The author considers the recent monograph by Václav Bůžek published in Czech and German devoted to the question of the interaction of the Bohemian aristocracy and the Habsburg courts in the sixteenth century. In his monograph, Václav Bůžek has amassed extensive source material and summarised the knowledge so far. Nevertheless, the author of the critical reflection at the same time shows the deficiencies that cheapen the book. They include on the one hand little critical work with the sources proving the presence of aristocrats from the Czech lands at the Habsburg courts (incorrect reading, factual errors in identification, a lack of clarity of the criteria) and on the other hand the problematic framing of the analysis itself of the court ceremonials by contemporary research on the political rituals in the Early Modern Period by means of defunct references, which fulfill the role of the formal methodological assurance without a real harmony with the cited studies and partially in contradiction to them. A difficulty of the publication is also stylistics, combining expert-sounding constructions that are empty of content with psychologizing and in places bizarre fictionalization of the described facts, which often leads to murky argumentation.